Performance of Activated Carbon from Date Seeds for Methylene Blue Treatment - Muhammad Fauzan Syafi Mohamed Foudi; Mohd Nur Aiman Syazani Huzairi; Mohd Adnan, Raudah; Dilaeleyana Abu Bakar Sidik (Multidisciplinary Applied Research and Innovation, 2024)
Products that employ methylene blue dyes in their manufacturing processes leak harmful substances into the environment as waste. Activated carbon is used as an adsorbent to treat methylene blue because of a unique characteristic that makes it capable of being an excellent adsorbent in the wastewater treatment process This research aims to develop an activated carbon using waste date seeds to treat the methylene blue. The characterization of date seed was carried out using FTIR to identify functional groups and chemical bonds involved and SEM analysis, to identify its morphology of activated carbon. It employed a chemical activation method to produce date seeds-activated carbon. Since increasing the amount of DSAC utilized decreases color more efficiently, it can be employed as an effective absorbent. The date seeds sample must be thoroughly processed to remove all excess chloride from KOH. Based on COD, turbidity, and color analysis, the value obtained increased proportionally with dosages 10,20,30, and 40g. DSAC adoption showed positive results for color removal but not for COD and turbidity. 40 g of DSAC achieves an excellent result, removing 96.61% of the color from methylene blue. As the dosage of DSAC used increased, a greater reduction of color achieve.